Public sector involvement in non-state governances for sustainable food systems—a biodiversity perspective - Talia Shalom; Tamar Dayan; Tamar Dayan; Eran Feitelson (Frontiers in Sustainable Food Systems)
The extensive use of natural resources in agri-food systems has widespread effects on biodiversity. Policies advanced to address these effects have largely failed to reduce the rate of biodiversity loss significantly. Current strategies for biodiversity and sustainable food systems increasingly advance two modes of non-governmental governance, Multi-Stakeholder Initiative (MSI) and Voluntary Sustainability Standards (VSS), among their key policy tools. In this paper, we analyze public-private VSS and MSI governances related to biodiversity enhancement and discuss how and whether they have shaped the ground for the wide-scale use of MSIs and VSSs as suggested in post-2020 strategies. Our analysis highlights the importance of governments’ commitment to biodiversity enhancement as a prerequisite for effective and robust governance. We also emphasize the need for innovative regulation to supervise and advance various VSS and MSI simultaneously. Our findings indicate that up to 2020, governments’ main motivations for being involved in food governance were the advancement of food safety regulation or economic development rather than biodiversity enhancement. Accordingly, public involvement in VSS and MSI at the global scale does not necessarily provide rigorous biodiversity protection. In 2020, the EU established a comprehensive strategy for biodiversity and integrated its three-decades-long engagement with organic farming into it as a policy tool. This policy has diffused to local European food policy councils. However, the capital-intensive boost in a single VSS, leaves other biodiversity-oriented initiatives without substantive governmental support.